Dampak Gaya Kepemimpinan Demokratis, Disiplin Kerja Dan Lingkungan Kerja Terhadap Kinerja Pegawai Kantor Otoritas Bandar Udara Wilayah VI Padang - Hidayatullah, Syarif; Sopian, Sophan (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
At the Padang Region VI Airport Authority Office, there is a lack of communication between management and employees to simply ask about the conditions being faced by employees and a lack of holding meetings with employees to discuss problems to be faced and goals to be achieved by the Airport Authority Office. Air Region VI Padang so as to create a joint commitment to the tasks to be carried out. The objectives of the research are: (1) To find out how big the impact of democratic leadership style is on the performance of employees of the Padang Region VI Airport Authority Office, (2) To find out how big the impact of work discipline is on the performance of employees of the Padang Region VI Airport Authority Office. (3) To find out how big the impact of the work environment is on the performance of employees of the Padang Region VI Airport Authority Office. This research is included in the Quantitative type of research. The object of this research was carried out at the Padang Region VI Airport Authority Office, Jl. MR. Sutan Moh. Rasjid – District. Batang Anai Ketaping Padang Pariaman, West Sumatra 25586. The population in this study was 101 employees of the Padang Region VI Airport Authority Office and a sample of 101. The types of data used were primary and secondary data. The analysis method is multiple linear regression analysis. The research results found: (1) The democratic leadership style partially has a positive and significant effect on employee performance at the Padang Region VI Airport Authority Office. (2) Work discipline partially has a positive and significant effect on employee performance at the Padang Region VI Airport Authority Office, (3) The work environment partially has a positive and significant effect on employee performance at the Padang Region VI Airport Authority Office Padang Region VI Airport Authority Office in improving employee performance by paying attention to democratic leadership style, work discipline and work environment in order to achieve high employee performance at work